Alzheimer’s Disease and Cardiovascular Disease: A Particular Association - Giacomo Tini; Riccardo Scagliola; Fiammetta Monacelli; Giovanni La Malfa; Italo Porto; Claudio Brunelli; Gian Marco Rosa (Cardiology Research and Practice)
Background and aim. During ageing, the prevalence of dementia, and especially of Alzheimer’s disease (AD) and cardiovascular disease (CVD), increases. The aim of this review is to investigate the relationship between AD and CVD and its risk factors, with a view to explain the underlying mechanisms of this association. Methods. This review is based on the material obtained via MEDLINE (PubMed), EMBASE, and Clinical Trials databases, from January 1980 until May 2019. The search term used was “Alzheimer’s disease,” combined with “cardiovascular disease,” “hypertension,” “dyslipidaemia,” “diabetes mellitus,” “atrial fibrillation,” “coronary artery disease,” “heart valve disease,” and “heart failure.” Out of the 1,328 papers initially retrieved, 431 duplicates and 216 records in languages other than English were removed. Among the 681 remaining studies, 98 were included in our research material on the basis of the following inclusion criteria: (a) the community-based studies; (b) using standardized diagnostic criteria; (c) reporting raw prevalence data; (d) with separate reported data for sex and age classes. Results. While AD and CVD alone may be considered deleterious to health, the study of their combination constitutes a clinical challenge. Further research will help to clarify the real impact of vascular factors on these diseases. It may be hypothesized that there are various mechanisms underlying the association between AD and CVD, the main ones being hypoperfusion and emboli, atherosclerosis, and the fact that, in both the heart and brain of AD patients, amyloid deposits may be present, thus causing damage to these organs. Conclusions. AD and CVD are frequently associated. Further studies are needed in order to understand the effect of CVD and its risk factors on AD in order to better comprehend the effects of subclinical and clinical CVD on the brain. Finally, we need to clarify the impact of the underlying hypothesized mechanisms of this association and to investigate gender issues.